Impact of anxiety on the prevalence of tobacco use among medical students, Ain Shams University, Egypt. Issue 3 (July 2018) - El-Rasheed, Amany H.; Radwan, Doaa N.; Elhabiby, Mahmoud M.; Nosir, Hebatallah M.; Elnemais Fawzy, Michael
Abstract : Objective: To assess the prevalence of tobacco use in a sample of medical students and house officers at Ain Shams University, Egypt, and to assess the impact of anxiety on tobacco use in this sample. Materials and methods: A cross-sectional observational study was set out to assess the prevalence of tobacco use in a sample of 539 medical students (115 in the first year, 244 in the sixth year, and 180 in house officers) at the Faculty of Medicine, Ain Shams University, Egypt, during the interval from April 2013 to July 2013. The tools used were Global Health Professional Students Survey, Hamilton Rating Scale for Anxiety, and Modified Fagerström Test for Nicotine Dependence. Results: The prevalence of smoking among the medical students and house officers was 29.8%. The rate of smoking was found to increase significantly as the medical students progress through the years of their study. So, there was a statistically highly significant difference regarding smoking status with the first year students showing the highest percent of never smoking (78.5%) and house officers showing the highest percent of ever and current smoking (31.6 and 10.2%), respectively. There was a statistically highly significant difference regarding anxiety among medical students and house officers with house officers having the highest percent of mild anxiety (69.3%), while the first year students have the highest percent of moderate and severe and grossly severe anxiety (42.4 and 7.1%, respectively). There was a statistically highly significant difference regarding tobacco cigarette smoking in relation to anxiety in the first year students but not in the other groups. However, there was no statistically significant difference ( P >0.05) regarding the severity of nicotine dependence in relation to the severity of anxiety (among surveyed medical students and house officers). Conclusion: The rate of tobacco cigarette smoking is significantly increased as the medical students who progress through the years of their study being 21.5, 24.6 and 41.8% in the first, sixth year students and house officers, respectively. Anxiety had an impact on smoking in the first year students only.